Friedrich Schleiermacher's philosophy of religion: historical and contemporary perspectives - Lang, Stefan; Viertbauer, Klaus (Routledge studies in the philosophy of religion, 2025)
"This volume provides a comprehensive account of Friedrich Schleiermacher's philosophy of religion. The contributors cover the historical context of Schleiermacher's work, specific aspects of his philosophy of religion, and the ways that his work can contribute to contemporary debates. Friedrich Schleiermacher is considered one of the outstanding representatives of 19th-century Protestant theology. This volume brings together scholars from both continental and analytic traditions to explore Schleiermacher's preeminent role in post-Kantian philosophy of religion. The chapters are divided into three thematic sections. The first section situates Schleiermacher in the context of the 19th-century philosophy of religion. These chapters analyse his relation to thinkers such as Kant, Fichte, Hegel, Schelling, Kierkegaard, and Heidegger, as well as to prominent theologians in the Protestant and Catholic traditions. The second section explores different aspects of Schleiermacher's philosophy of religion such as absolute dependence or religious feelings. Finally, section three addresses how Schleiermacher's insights can contribute to contemporary philosophy of religion. These chapters address current debates, particularly on religious experience, feminism, and philosophy of emotions. Friedrich Schleiermacher's Philosophy of Religion will be of interest to scholars and advanced students working in philosophy of religion, history of philosophy, and 19th-century religious thought"--